Prognostic value of heart rate variability indexes with regard to acute postinfarction aneurysm of left ventricle formation - S. M. Kyselov (Zaporožskij Medicinskij Žurnal)
Prediction of Q-wave myocardial infarction complications in acute period is an actual problem of modern cardiology.